Half-metallic Alloys Fundamentals and Applications - Galanakis, I.; Dederichs, P.H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Half-metals are particular ferromagnetic materials which can be considered as hybrids between metals and semiconductors. A particular feature of these materials is that electrons at the Fermi level show complete spin polarization making them prime targets for research into suitable divices for spin electronics. This book is both an introduction and state-of-art survey of the latest advances in the understanding and applications of Heusler alloys and related compounds.
Half-Metallicity and Slater-Pauling Behaviour in the Ferromagnetic Heusler Alloys -- Role of Structural Defects on the Half-Metallic Character of Heusler Alloys and Their Junctions With Ge and GaAs -- Magnetism And Structure of Magnetic Multilayers Based on the Fully Spin Polarized Heusler Alloys Co2NnGe and Co2MnSn -- Epitaxial Growth of NiMnSbon GaAs by Molecular Beam Epitaxy -- Growth and Magnetotransport Properties of Thin Co2NnGe Layered Structures -- Surface Segregation And Compositional Instability at The Surface of Half-Metal Ferromagnets and Related Compounds -- Heusler Alloyed Electrodes Integrated in Magnetic Tunnel-Junctions -- Half-Metallic Ferromagnetism and Stability of Transititon Metal Pnictides And Chalcogenides -- Materials Design and Molecular-Beam Epitaxy of Half-Metallic Zinc-Bende CrAs and The Heterostructures.
Keywords: Materials science; Solid state physics; Magnetism; Magnetic materials; Spectroscopy; Microscopy; Metals; Materials Science; Metallic Materials; Solid State Physics; Spectroscopy and Microscopy; Magnetism, Magnetic Materials; Electronic books